Blue code: Is it a real emergency? - (:unkn) unknown (My University, 2014)
BACKGROUND: Cardiac arrests in hospital areas are common, and hospitals have rapid response teams or "blue code teams" to reduce preventable in-hospital deaths. Education about the rapid response team has been provided in all hospitals in Turkey, but true "blue code" activation is rare, and it is abused by medical personnel in practice. This study aimed to determine the cases of wrong blue codes and reasons of misuse. METHODS: This retrospective study analyzed the blue code reports issued by our hospital between January 1 and June 1 2012. A total of 89 "blue code" activations were recorded in 5 months. A "blue code" was defined as any patient with an unexpected cardiac or respiratory arrest requiring resuscitation and activation of a hospital alert. Adherence to this definition, each physician classified their collected activation forms as either a true or a wrong code. Then, patient data entered a database (Microsoft Excel 2007 software) which was pooled for analysis. The data were analyzed by using frequencies and the Chi-square test on SPSSv16.0. RESULTS: The patients were diagnosed with cardiopulmonary arrest (8), change in mental status (18), presyncope (11), chest pain (12), conversive disorder (18), and worry of the staff for the patient (22). Code activation was done by physicians in 76% of the patients; the most common reason for blue code was concern of staff for the patient. CONCLUSION: The findings of this study show that more research is needed to establish the overall effectiveness and optimal implementation of blue code teams.
Keywords: Blue code; Code activation; Hospital arrest